Does Double-layer Application of a Universal Adhesive Affect Its Bonding to Different Tooth Substrates? - Tekce, Aybuke Uslu; Atalay, Cansu; Dursun, Meltem N.; Ertan, Atilla; Yazici, A. Ruya (Marmara Univ, Inst Health Sciences, 2021)
Objective: The aim of this study was to evaluate the effect of a single or double layer application of a Universal adhesive on bond strength to different tooth substrates. Methods: Seventy-two extracted sound human teeth were used for the study. The teeth were divided into three groups according to tooth substrates; enamel, coronal and radicular dentin (n=24). The roots of the teeth were separated from the crowns and then abraded to obtain flat surfaces. The specimens were randomly allocated into 2 groups in accordance with application layers of universal adhesive (n=12). The universal adhesive, Adhese Universal was applied in self-etch mode as single - or double-layer to different substrates. Following the adhesive application, enamel, coronal and radicular dentin substrates were restored with a resin composite (Tetric N-Ceram). The specimens were subjected to shear bond strength (SBS) test after storage in distilled water (37celcius, 24 h). Representative fractured and interface samples from each group were examined by a scanning electron microscope. The data were analyzed using two-way ANOVA(alpha = 0.05). Results: There was no statistically difference in SBS values between single - and double-layer applications of the tested universal adhesive on different dental substrates (p>0.05). Whilst no difference was occurred between the different dental substrates in the single-layer application (p>0.05), double-layer application on coronal dentin presented significantly higher bond strength than enamel (p<0.05). Conclusion: Double-layer application of the tested universal adhesive did not improve the bond strength regardless of different dental substrates.
Keywords: Universal adhesive; Shear bond strength; Double-layer application